A Case of Rathke’s Cleft Cyst Associated with Transient Central Adrenal Insufficiency and Masked Diabetes Insipidus - Masahiro Asakawa; Rina Chin; Yoshihiro Niitsu; Tetsuo Sekine; Arisa Niwa; Atsuko Miyake; Naoko Inoshita; Mitsunobu Kawamura; Yoshihiro Ogawa; Yukio Hirata (Case Reports in Endocrinology)
A 73-year-old woman admitted to our hospital because of headache, poor appetite, malaise, weight loss, and vomiting was found to have central adrenal insufficiency and thyrotoxicosis due to silent thyroiditis. Polyuria developed after replacement with glucocorticoid (masked diabetes insipidus), which was controlled with nasal administration of desmopressin. Magnetic resonance imaging of the brain showed a large cystic pituitary mass (18 × 18 × 12 mm) extending suprasellarly to the optic chiasm. Transsphenoidal surgery revealed that the pituitary tumor was Rathke’s cleft cyst. Following surgery, replacement with neither glucocorticoid nor desmopressin was needed any more. Therefore, it is suggested that Rathke’s cleft cyst is responsible for the masked diabetes insipidus and the central insufficiency. Furthermore, it is speculated that thyrotoxicosis with painless thyroiditis might induce changes from subclinical adrenal insufficiency to transiently overt insufficiency.